2007
DOI: 10.1103/physrevc.75.064611
|View full text |Cite
|
Sign up to set email alerts
|

Search for the fade out of a collective enhancement of the nuclear level density

Abstract: The fade out of a collective enhancement of the nuclear level density is predicted (by an SU3 shell model) to give rise to a clear signature in the evolution of the spectral shape of evaporated charged particles with excitation energy. We have searched for this signature in the spectra of α particles emitted from 178 Hf compound nuclei, with excitation energies between 54 and 124 MeV, formed in 18 O+ 160 Gd fusion reactions. The Gammasphere spectrometer provided us with the ability to construct channel-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Collective excitations that can be expressed as a coherent superposition of single-particle excitations are expected to disappear at higher excitation energies, if the nuclear temperature becomes comparable with the energies of single-particle excitations [15]. However, the energy range, where this happens, is still under debate, since the available experimental indications are rather indirect and contradictory [16,17].…”
Section: Salient Features Of Nuclear Level Densitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Collective excitations that can be expressed as a coherent superposition of single-particle excitations are expected to disappear at higher excitation energies, if the nuclear temperature becomes comparable with the energies of single-particle excitations [15]. However, the energy range, where this happens, is still under debate, since the available experimental indications are rather indirect and contradictory [16,17].…”
Section: Salient Features Of Nuclear Level Densitiesmentioning
confidence: 99%
“…The back-shift parameter of the Fermi-gas part is then given by the usual matching conditions. The fade out of the collective enhancement remains an open problem, but experimental results [16] and theoretical arguments [17] suggest that this feature is rather inconspicuous. MeV, and the level density in the Fermi-gas regime is enhanced by about a factor of 50 with respect to the conventional composite Gilbert-Cameron level density.…”
Section: Composite Gilbert-cameron Level Densitymentioning
confidence: 99%
“…Other authors have suggested that collective effects are not necessary to reproduce EvR cross sections away from the N = 126 shell because the effects are weak [15] or because the fission barriers are much smaller than predicted by theory [16]. Additionally, α-particle spectra were poorly reproduced when CELD was considered [17]. It is clear that further investigation into the CELD phenomenon is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…With smoothing shell gaps, it is harder to distinguish between rotational and intrinsic motion. Recent experiments in nuclei, where low-lying collective excitations are well known, did not find clear phenomena of collective enhancement and its fade-out [48].…”
Section: Shell-model Predictions and Mean-field Combinatoricsmentioning
confidence: 99%